Establishment and comparative analysis of Agrobacterium-mediated genetic transformation systems for Actinidia valvata and Actinidia chinensis - Xia, Junyao; Shu, Jinfang; Lin, Su; Zhu, Junjie; Lin, Fangbin; Fang, Runxuan; Huo, Liuqing; Liu, Jinhua; Xu, Kai; Ma, Haijie (Frontiers in Plant Science, 2026)
Kiwifruit (Actinidia spp.) is an economically important horticultural crop, yet functional genomics and molecular breeding efforts remain limited by low transformation efficiency, particularly in recalcitrant genotypes. In this study, Agrobacterium-mediated transformation systems were established and systematically optimized for Actinidia chinensis and Actinidia valvata. The optimized Agrobacterium tumefaciens GV3101 system achieved a 24% transformation efficiency in A. chinensis leaf explants, enabling complete plant regeneration within five months. In contrast, A. valvata showed only 4% efficiency, and its transformed call failed to initiate shoot organogenesis. To overcome this limitation, Agrobacterium rhizogenes K599-based methods were developed. The tissue culture system induced transgenic hairy roots at a rate of 68.7% without exogenous hormones, while a tissue culture-free protocol based on high-pressure propagation of woody stems reduced the transformation cycle to 4–5 weeks with 50% efficiency. Stable transgene integration and expression were confirmed by GFP fluorescence, PCR, and sequencing. Collectively, these transformation systems provide rapid, efficient, and reproducible tools that will substantially advance gene functional studies and molecular breeding in different kiwifruit species.